Intrinsic Business Cycles with Pro-Cyclical R&D - Patrick Francois; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2006)
Recent empirical work finds that R&D expenditures are quite procyclical, even for firms that are not redit-constrained during downturns. This has been taken as strong evidence against Schumpeterian-style theories of business cycles that emphasize the idea that downturns in production may be good times to allocate labor towards innovative activities. Here we argue that the procyclicality of R&D investment is, in fact, quite consistent with at least one of these theories. In our analysis, we emphasize three key features of R&D investment relative to other types of innovative activity: (1) it uses knowledge intensively, (2) it is a long-term investment with uncertain applications and (3) it suffers from diminishing returns over time.
Keywords: E3; O3; O4; 330; Schumpeterian; R&D investment; endogenous cycles; endogenous growth